The use of 2D and 3D information in a perceptual-cognitive judgement task - Put, K.; Wagemans, J.; Spitz, J.; Armentereos Gallaardo, M.; Williams, A. M.; Helsen, W. F. (Journal of Sports Sciences, 2015)
We examined whether the use of three-dimensional (3D) simulations in an off-field offside decision-making task is beneficial compared to the more widely available two-dimensional (2D) simulations. Thirty-three assistant referees, who were all involved in professional football, participated in the experiment. They assessed 40 offside situations in both 2D and 3D formats using a counterbalanced design. A distinction was made between offside situations near (i.e., 15 m) and far (i.e., 30 m) from the touchline. Subsequently, a frame recognition task was performed in which assistant referees were asked to indicate which of the five pictures represented the previous video scene. A higher response accuracy score was observed under 3D (80.0%) compared to 2D (75.0%) conditions, in particular for the situations near the touchline (3D: 81.8%; 2D: 72.7%). No differences were reported between 2D and 3D in the frame recognition task. Findings suggest that in highly dynamic and complex situations, the visual system can benefit from the availability of 3D information, especially for relatively fine, metric position judgements. In the memory task, in which a mental abstraction had to be made from a dynamic situation to a static snapshot, 3D stereo disparities do not add anything over and beyond 2D simulations. The specific task demands should be taken into account when considering the most appropriate format for testing and training.